Validity of Check Point Inhibitor (PD-1 and PD-L1) in Diagnosis of Gastric Adenocarcinoma Using Modified Tissue Elisa - Hind H. Al-Ammiri, Mohammed M. Mohammed, Ali Abdul Hussein, Ameer Dhahir Hameedi (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Checkpoint inhibitors (PD-1, PD-L1) are revolutionizing the oncology disease management process. Despite the fact that gastric cancer is a common malignancy with a poor prognosis, relatively little attention has been drawn and attracted to the treatment and diagnosis of this disease by using checkpoint inhibitor. James P. Allison and Tasuku Honjo were awarded the the Nobel Prize in Physiology and Medicine for their developments in fundamental science enabling checkpoint inhibitor therapies. Checkpoint inhibitor overexpression has been related to gastric cancer progression and clues for developing therapeutic goals as well as may provide diagnostic markers for gastric cancer. Aims: The aims of this study are firstly to detection of Checkpoint Inhibitors (PD-1, PD-L1) as novel diagnostics and prognostics markers first time in the world. Secondly, to investigate the validity of using (a modified tissue ELISA method) as a rapid, sensitive, low cost and specific diagnostic method in patients with gastric cancer. Patients and methods: Thirty gastric cancer patients were among patients who attending the Histopathology section -GIT hospital and Histopathology department- Teaching laboratories/ medical city teaching complex Baghdad / Ministry of Health, during the period from August 2020 to April 2021. Another 30 patients diagnosed with benign tumor, In addition, 30 apparently healthy people were chosen as a healthy control group. For these three groups, PD-1, PD-L1, using tissue ELISA technique was carried out. Results: The current study showed that the mean values of PD-1 in tissues of gastric cancer patients (133.413±53.126) was significantly higher (P=0.0001) in it in comparison to both benign tumor group (29.905±12.634) and control healthy group (21.775±12.489); for PD-L1 that the mean values of PD-L1 in tissues of gastric cancer patients (151.175±47.641) was significantly higher (P=0.0001) in it in comparison to both benign tumor group (72.565±9.945) and control healthy group (82.102±12.642); using receiver operating characteristic curve (ROC) area, which showed that area under the curve for PD-1 was (1.000) (p value 0.0001), while area under the curve for PDL-1 was (0.913) (p value 0.0001) and The cut off value for PD-1 associated with highest sensitivity and specificity (100%) was 40.2 ng/ml. The cut off value for PDL-1 associated with sensitivity (80%) and specificity (80%) was 51.6ng/ml. Conclusions: The present study showed that Checkpoint inhibitors (PD-1, PD-L1) values were significantly higher in patients affect with malignant gastric adenocarcinoma which may check a possible role of this marker in the progressing of the disease, furthermore the maximum sensitivity obtained from Checkpoint inhibitors (PD-1, PD-L1) was by using a cut off values equal to (40.2 ng/ml; 51.6 ng/ml) respectively. Therefore, Checkpoint inhibitors (PD-1, PD-L1) may be promising diagnostic tools especially at early stages and among patients at in promotion risk.